Why digital administrative systems create extra work and demoralize us: A study of performativity and decontextualization caused by Unikum in Swedish preschools. (April 2021) - Ledin, Per; Machin, David
Abstract: It is now common for public institutions, and other organizations, to be administrated and managed through digital systems. Such systems are aligned with a discourse of positivity, of doing things better, more effectively. In this paper, using multimodal critical discourse analysis, we analyze one digital system used in Swedish preschools called Unikum, built around the national targets in the new national curriculum. Our analysis considers the affordances of the digital system, the uses to which these are put, and the designs of its interfaces. Such systems set up a kind of information infrastructure where things and processes are coded and classified, providing locked-down positions, infused with power, where there is only one way of construing the world. We show how Unikum brings a marketized, customer oriented, ideology of teaching and learning into preschools, displaying a bright and optimistic world where all children are developing. This leads to incredible levels of performativity as teachers must communicate constantly using the codifications carried by the system as if everything was improving. The process comes at a cost of side-lining professional skills and also the very children themselves.